2016
DOI: 10.3390/toxins8100273
|View full text |Cite
|
Sign up to set email alerts
|

Different Toxicity Mechanisms for Citrinin and Ochratoxin A Revealed by Transcriptomic Analysis in Yeast

Abstract: Citrinin (CIT) and ochratoxin A (OTA) are important mycotoxins, which frequently co-contaminate foodstuff. In order to assess the toxicologic threat posed by the two mycotoxins separately or in combination, their biological effects were studied here using genomic transcription profiling and specific live cell gene expression reporters in yeast cells. Both CIT and OTA cause highly transient transcriptional activation of different stress genes, which is greatly enhanced by the disruption of the multidrug exporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Furthermore, the genes of icdA , acoB , sdh1 and sdh3 were all up‐regulated, especially, the relative expression of sdh1 in Y. lipolytica Y‐2 treated with OTA was 14.6 folds higher than the control (Figure h). These results were consistent with the reports that some genes of TCA cycle in S. cerevisiae such as IDP3 (encoding peroxisomal NADP‐dependent IDH), were up‐regulated to provide more energy to defend against OTA stress (Vanacloig‐Pedros et al, ). This implies that energy supply for Y. lipolytica Y‐2 by TCA cycle and respiratory chain was enhanced to defend against the oxidative stress caused by OTA.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, the genes of icdA , acoB , sdh1 and sdh3 were all up‐regulated, especially, the relative expression of sdh1 in Y. lipolytica Y‐2 treated with OTA was 14.6 folds higher than the control (Figure h). These results were consistent with the reports that some genes of TCA cycle in S. cerevisiae such as IDP3 (encoding peroxisomal NADP‐dependent IDH), were up‐regulated to provide more energy to defend against OTA stress (Vanacloig‐Pedros et al, ). This implies that energy supply for Y. lipolytica Y‐2 by TCA cycle and respiratory chain was enhanced to defend against the oxidative stress caused by OTA.…”
Section: Discussionsupporting
confidence: 91%
“…It was reported that some genes associated with antioxidant metabolism of Arabidopsis thaliana leaf were up‐regulated to defend against oxidative stress caused by OTA (Y. Wang et al, ). Also, OTA could induce the expression of some drug transport genes to expel the toxin from Saccharomyces cerevisiae and alleviate its toxicity (Vanacloig‐Pedros, Proft, & Pascual‐Ahuir, ). Furthermore, some genes associated with detoxification of xenobiotics and some pathogenesis‐related genes involved in the resistance of cells were up‐regulated in A. thaliana leaf in response to OTA treatment (Y. Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we chose instead to search for related pathways from a holistic perspective because transcriptome data can quickly and economically supply accurate genome information, particularly in identifying the effects of biological pathways and processes [51,52]. Elena et al (2016) used transcriptomic analysis to reveal the different toxicity mechanisms of OTA and citrinin [53]. Hence, we used a transcriptomic study to provide a genome-wide biological view of changes that occurred after treatment of differentiated Caco-2 cells with different concentrations of OTA.…”
Section: Discussionmentioning
confidence: 99%
“…Other transcription factors that bind to P MCH4 are Cad1p and Yap1p (stress response), Yap7p (unknown function) and Pho2p (an activator involved in several metabolic pathways). Previous reports indicated that MCH4 is upregulated in response to osmotic and possibly other kinds of stress (Causton et al, 2001;Jelinsky et al, 2000;Epstein et al, 2001;Vanacloig-Pedros et al, 2016).…”
Section: Regulation Of Mch4mentioning
confidence: 97%